The Effect of Concentration of Flour, Green Mustard Pasta (Brassica Juncea) On The Characteristics of Ice Cream - Sholikah Dwi Kartika; Ida Agustini Saidi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of the concentration of green mustard flour (Brassica juncea) and green mustard paste on the characteristics of ice cream. The levels are P1 0% Green Mustard Flour and 0% Green Mustard Paste, P2 3% Green Mustard Flour, P3 6% Green Mustard Flour, P4 9% Green Mustard Flour, P5 12% Green Mustard Flour, P6 15% Green Mustard Paste, P7 20% Green Mustard Paste, P8 25% Green Mustard Paste and P9 30% Mustard Paste. The variables measured were organoleptic tests on aroma, taste, color, texture and overall acceptance. The results showed that the concentration of green mustard flour and green mustard paste had a significant effect on organoleptic tests (aroma, taste, color, texture and overall acceptance). The best treatment parameters in this study were ice cream with a concentration of mustard paste 25% (P8) which showed an organoleptic aroma value of 3.3 (slightly typical of mustard greens - not typical of mustard greens), organoleptic taste of 2.9 (no taste typical of mustard greens - slightly taste typical of mustard greens), color organoleptic 3.6 (Slightly green – green), texture organoleptic 3.9 (soft), organoleptic overall reception 3.4 (slightly like – like).